IMPLEMENTING THE CULTURAL DIMENSIONS PROPOSED BY GERARD HOFSTEDE FOR INTERCULTURAL MULTILUNGIAL COMMUNICATION - Zhussupova R. F.,; Kosherova K. K.,; Dauletova N. M.,; Dyachenko O. V.,; Tolegen A., (Scientific Journal of Pedagogy and Economics, 2019)
These days given with the enlargement of international tourism, business enterprise and global work mobility, intercultural communication has become a comprehensive part of daily lifetime of most individuals. This study is devoted to efficient intercultural communication, obstacles and strategies to increase the efficiency of intercultural multilingual communication. We describe the means by which we can become efficient in intercultural communication, thereby to be intercultural competent, how an individual can obtain understanding of a culture, corresponding communication competence and relation without which realization of different culture is not possible. The objective of this research is to investigate basic aspects the theory of five cultural dimensions created by Gerard Hendrik Hofstede with regard to its efficiency in multilingual Kazakhstani society. His well-known theory of Five Cultural Dimensions covers a framework of behavior, prospect and valuation tendencies that are related with 50 cultures around these structures, moreover, each ingrained in a key issue with which all communities have to manage. These days, Hofstede’s theory of Cultural Dimensions is a precise analysis of current world companies and corporations, universities and different cross-cultural facilities to reach greater comprehension of members in universal context. We also characterized various types and kinds of culture such as power distance, collectivism and individualism, femininity and masculinity, uncertainty avoidance, long-term and short-term orientation and finally indulgence and restraint. The knowledge regarding the aspects of intercultural interaction and its efficiency included in this paper can be useful for all the humankind who work in international organizations where they are forced to interact with various nationality people, they supposed to solve issues which is impracticable without efficient interaction. Nonetheless, the study exploring proves that the problem of intercultural communication is discussed acrossthe-board. We strongly believe that the question of efficient intercultural multilingual communication must be included in business trainings as well as master-classes in international organizations.